ANALYSIS OF ASSOCIATIVE SOCIAL INTERACTION PROCESSES BETWEEN THE STUDENT COUNCIL IN JUNIOR HIGH - aziz, abdul (Jurnal Pendidikan Sosiologi dan Humaniora, 2019)
The study aims to determine the associative cooperation between board and accommodation OSIS SMP Islam Ashabul Kahfi Pontianak in West Borneo period 2015-2016. The method used is descriptive with problem solving procedures investigeted by describing or depicting the state of the subject or object of research. In the study sample are seven members of the total board OSIS twenty four members. The analysis showed that the cooperation between board OSIS has worked well for the cooperation ehich is always enhanced by the whole OSIS and coaching are continually done by coach OSIS SMP Islam Ashabul Kahfi Pontianak, although still les than perfect because of several obstacles that accur within board OSIS.